Low ethanol consumption induces enhancement of insulin sensitivity in liver of normal rats - Furuya, Daniela Tomie; Binsack, Ralf; Onishi, Mary Emy; Seraphim, Patricia Monteiro; Machado, Ubiratan Fabres (Elsevier, 2005)
Moderate amounts of alcohol intake have been reported to have a protective effect on the cardiovascular system and this may involve enhanced insulin sensitivity. We established an animal model of increased insulin sensitivity by low ethanol consumption and here we investigated metabolic parameters and molecular mechanisms potentially involved in this phenomenon. For that, Wistar rats have received drinking water either without (control) or with 3% ethanol for four weeks. The effect of ethanol intake on insulin sensitivity was analyzed by insulin resistance index (HOMA-IR), intravenous insulin tolerance test (IVITT) and lipid profile. The role of liver was investigated by the analysis of insulin signaling pathway, GLUT2 gene expression and tissue glycogen content. Rats consuming 3% ethanol showed lower values of HOMA-IR and plasma free fatty acids (FFA) levels and higher hepatic glycogen content and glucose disappearance constant during the IVITT. Neither the phosphorylation of insulin receptor (IR) and insulin receptor substrate-1 (IRS-1), nor its association with phosphatidylinositol-3-kinase (PI3-kinase), was affected by ethanol. However, ethanol consumption enhanced liver IRS-2 and protein kinase B (Akt) phosphorylation (3 times, P < 0.05), which can be involved in the 2-fold increased (P < 0.05) hepatic glycogen content. The GLUT2 protein content was unchanged. Our findings point out that liver plays a role in enhanced insulin sensitivity induced by low ethanol consumption. © 2005 Elsevier Inc. All rights reserved.
Keywords: Akt/PKB; Hepatic glycogen; Insulin receptor substrate-2; Insulin sensitivity; Low-ethanol intake; alcohol; drinking water; fatty acid; glucose; glucose transporter 2; glycogen; insulin; insulin receptor; insulin receptor substrate 1; insulin receptor substrate 2; lipid; phosphatidylinositol 3 kinase; protein kinase B; alcohol consumption; animal experiment; animal tissue; controlled study; fatty acid blood level; glucose homeostasis; glucose utilization; glycogen analysis; glycogen liver level; insulin resistance; insulin sensitivity; intravenous glucose tolerance test; lipid analysis; liver function; male; metabolic parameters; nonhuman; protein content; protein folding; protein phosphorylation; rat; 1-Phosphatidylinositol 3-Kinase; Alcohol Drinking; Animals; Blotting, Northern; Blotting, Western; Body Weight; Cholesterol; Eating; Ethanol; Fatty Acids, Nonesterified; Gene Expression; Glucose Transporter Type 2; Glycogen; Insulin; Insulin Resistance; Intracellular Signaling Peptides and Proteins; Lipoproteins; Liver; Male; Monosaccharide Transport Proteins; Phosphoproteins; Phosphorylation; Protein-Serine-Threonine Kinases; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-akt; Rats; Rats, Wistar; Receptor, Insulin; Triglycerides; Animalia; Rattus norvegicus